O imaginário do professor sobre o ensino de língua portuguesa : uma relação contraditória - Linck, Ieda Márcia Donati (2011)
The present study, based on the French Discourse Analysis (DA) perspective, focus on the language imaginary constituted in the discourse of Portuguese language teachers about the question Is there a difference between teaching and learning? The linguistic materialization is on the hints obtained from the interviews, which were answered by ten teachers from basic to higher education in the city of Cruz Alta / RS. Among other questions they answered What do you believe to make your students learn? In order to reach the discursive functioning this paper has been divided into three parts. In the first one, we present the review of the conceptions of language and discourse according to the theory, which are based on Foucault, Pêcheux, Orlandi, Indursky, among others, who allow us to affirm that the meanings are beyond the text, in the sense that they show life experience, in the teachers particular universe, producing similar effects regarding the subjecting, i.e., the teachers knowledge preexisting the discourse, considered as effect of senses among speakers (PÊCHEUX, 1993, p. 1993). We also consider the concept of fluid and imaginary languages, necessary knowledge in order to analyze the fluid meaning in the teachers discourse regarding their conception of which language to teach. In the second part, we present some concepts of the Discourse Analysis theory: theoretical considerations about discourse and ideology, discursive formation; formation ideology, language, subject and sense effect; subject-form; subject-position; interdiscourse and discursive memory, basic concepts for the analysis development. Finally, in the third part we present one block of discursive sequences (DS), divided into four cuttings, indicating the several conceptions of language present in the teacher discourse, which suggest the analysis of the subject-position by the contiguity, showing the discursive functioning from the regularity of some uses in the discourse, linguistically marked. As a result of the study, in the teacher discursive formation, we observe the subject-position 1: conservative teacher as well as the subject-position 2: innovative teacher, both of them in an internal contradictive process, which indicates the teaching of an imaginary language, possible to be transmitted and assimilated, and this way can be understood as out of the subject